Iwolefu Funeral Insurance and the Socioeconomics of Burial Ceremony in Ikorodu area of Lagos State - Faruq Idowu Boge (Yoruba Studies Review)
Death is an inevitable aspect of human existence. Human beings have evolved the custom of honouring the deceased with organized burial arrangements. Each society, therefore, has a different tradition for funeral arrangements and burial ceremonies. Among the Yoruba people, the deceased is honored with elaborate funeral arrangements incurring huge expenses. Traditionally, these expenses are borne by the deceased’s lineage. The Ikorodu (Remo) sub-ethnic Yoruba group has a traditional form of funeral insurance that makes funeral arrangements and expenses a communal responsibility. This study microscopically examines aspects of burial arrangements among the people. It specifically concentrates on the traditional funeral insurance practice, locally known as iwolefu, among the people. The study argues that the traditional funeral insurance practice is among the main instruments by which the institutions of ẹbí (family) and ìdílé (lineage) are preserved among the aborigines of the Ikorodu area. The study uses historical and ethnographical approaches to data collation and interpretation.